Decision-Making for Rewilding: An Adaptive Governance Framework for Social-Ecological Complexity - Butler, James R. A.; Marzano, Mariella; Pettorelli, Nathalie; Durant, Sarah M.; du Toit, Johan T.; Young, Juliette C. (Frontiers in Conservation Science, 2021)
Rewilding can be defined as the reorganisation or regeneration of wildness in an ecologically degraded landscape with minimal ongoing intervention. While proposals for rewilding are increasingly common, they are frequently controversial and divisive amongst stakeholders. If implemented, rewilding initiatives may alter the social-ecological systems within which they are situated and thus generate sudden and unforeseen outcomes. So far, however, much of the discourse on the planning and implementation of rewilding has focused on identifying and mitigating ecological risks. There has been little consideration of how rewilding could alter the human components of the social-ecological systems concerned, nor governance arrangements that can manage these dynamics. This paper addresses this gap by proposing a generic adaptive governance framework tailored to the characteristics of rewilding, based on principles of managing complex social-ecological systems. We integrate two complementary natural resource governance approaches that lend themselves to the contentious and unpredictable characteristics of rewilding. First, adaptive co-management builds stakeholder adaptive capacity through iterative knowledge generation, collaboration and power-sharing, and cross-scale learning networks. Second, social license to operate establishes trust and transparency between project proponents and communities through new public-private partnerships. The proposed framework includes structural and process elements which incorporate a boundary organisation, a decision-into-practice social learning exercise for planning and design, and participatory evaluation. The latter assesses rewilding outcomes and pre-conditions for the continuation of adaptive governance and conservation conflict resolution.